Sentidos do grafite: um estudo sobre a identidade do jovem do Vale do Paraíba - Oliveira, Lais Claro (2018)
The phenomenon of inscriptions made on the walls dates since the cave times, when man recorded with images and symbols his daily life, therefore the history of civilization. In ancient times, graffiti has started to characterize and compose complaints, resistance and subversion movements. Widely spread throughout the world, graffiti was decriminalized in 2011 in Brazil by Law 12408 which differed it from vandalism. However, even after the effervescence of urban interventions and the inclusion of new connotations such as leisure and work, the production is still considered marginalized and carries various stigma to those who draw graffiti, specially in regions far away from large urban centres. In Paraíba Valley, in the countryside of São Paulo, a study carried out in 2015 allowed to observe that even in the face of regulatory and territory exclusion aspects, the practice of graffiti essentially led by young people has personal and social transformation power. Thus, in order to better understand the process of building the identity expression of the youth who resists and creates new ways of being in the contemporary urban context, the present study sought to respond: “How does the process of identification, resistance and creation of the young graffiti draftsman happen given the sociocultural identity policies of the territory of Paraíba Valley?”. The study is supported by the contributions of Critical Social Psychology and social constructs of the Identity analytical category proposed by Antonio da Costa Ciampa (1987). The technique of life history narrative was privileged as instrument, analyzed in the light of the Identity-Metamorphosis-Emancipation Syntagma (1987), according to the usual procedures of the identification studies in the category. The use of interviews with informants, field records and photographs of the productions of young draftsmen of Paraíba Valley was adopted to assist in the field characterization and its main issues. It has been understood that the practice of graffiti is permeated by the institutional commercial imprisoning logic of the territory, which influence the experiences and senses attributed by young people. Nevertheless, given that social space and metamorphosis intercalate, it was understood that creativity reveals to be a strategy of coping with the present contradictions and identity policies involved. It is expressed over youth by different artistic modalities and contexts, as well as in the organisation of independent collective events and actions, which retain communicative and critical capacity, and expand the possibilities of emancipatory movements